FINANCIAL TECHNOLOGY DAN CASHLESS PAYMENT SEBAGAI STRATEGI BISNIS PADA COFFEE SHOP DI KOTA DENPASAR - Ayu Indira Dewiningrat (JUIMA : JURNAL ILMU MANAJEMEN, 2022)
The purpose of this research is to understand the role of financial technology and cashless payments as a business strategy for coffee shops in Denpasar City. The research method used is qualitative, namely the research method used with a descriptive approach. This study uses primary data and secondary data in the form of interviews, observation, documentation. The research results obtained are that some coffee shop owners who implement cashless payment-based fintech are those who understand more that fintech is not just a transaction tool with digital payments. Despite the fact that many fintech roles are used in the business sector to assist business activities and in terms of financial literacy, such as financing and financial arrangements and others. Coffee shop owners also admit that applying fintech can make transactions easier, especially for consumers.